Peripheral artery disease in HIV-infected older adults on antiretroviral treatment in Thailand - L. Aurpibul (2018)
© 2018 British HIV Association Objectives: HIV infection has become a chronic disease requiring long-term treatment. Premature cardiovascular disease resulting from atherosclerosis in the HIV-infected population has been observed. We assessed the prevalence of peripheral artery disease (PAD), a common consequence of atherosclerosis, in HIV-infected patients aged ≥ 50 years receiving antiretroviral treatment (ART). Methods: This cross-sectional study was conducted in 12 community hospitals in Chiang Mai, Thailand. Inclusion criteria were as follows: (1) age ≥ 50 years, (2) positive HIV status, and (3) currently receiving ART. Age- and sex-matched hospital patients without documented HIV infection were enrolled as a comparison group. Clinical data were extracted from hospital records. Personal information and details of PAD-related symptoms were obtained through face-to-face interviews. The diagnosis of PAD was made using ankle-brachial index (ABI) measurement. Results: Seven hundred and twenty-four participants were enrolled in the study (362 HIV-infected patients and 362 patients in the comparison group). In the HIV-infected group, 43% were male; the mean (± standard deviation) age was 57.8 ± 5.6 years. The mean (± standard deviation) times from HIV diagnosis and ART initiation were 10.0 ± 4.3 and 8.6 ± 3.5 years, respectively. The prevalence of abnormal ABI (< 1.00) was significantly lower in the HIV-infected group than in the comparison group (20 versus 27%, respectively; P = 0.03), while that of PAD (ABI ≤ 0.90) was not significantly different between the two groups (5 and 7%, respectively). In the HIV-infected group, female sex and low body mass index were independently associated with abnormal ABI. Conclusions: The prevalence of PAD when measured by ABI in HIV-infected older adults was relatively low. A follow-up study to determine the incidence of PAD and its persistence with time is warranted.